Effects of tryptophan supplementation on performance, intestinal morphology and protein abundance of tight junction protein and indoleamine 2, 3-dioxygenase in weaned pigs - Pei Mao; Naizhi Hu; Mengmeng Gao; Lingping Zhao; Chengsheng Song; Wenfeng Ma (Czech Journal of Animal Science)
This study determined the effect of tryptophan (Trp) supplementation on the protein abundance of intestinal tight junction and indoleamine 2, 3-dioxygenase (IDO) in weaned pigs. Ninety-six White × Landrace × Duroc piglets (5.31 ± 0.54 kg) were selected in a growth trial and the experiment lasted for 30 days. The basal diet based on corn and soybean contained Trp at 2.4 g/kg. The dietary treatments consisted of a basal diet or a basal diet + 500 mg/kg Trp. On the 31st day, 12 pigs (1 pig per pen) were randomly selected and slaughtered in order to collect samples for subsequent analysis. Dietary supplementation with Trp improved the villus height and protein abundance of Zonula occludens protein 1 (ZO-1) in the duodenum and the jejunum (P < 0.05), increased the protein abundance of Claudin-1 in the duodenum (P < 0.05) and IDO expression in the ileum (P < 0.05), and reduced the urea nitrogen concentration in the serum and the ZO-1 protein abundance of the ileum in weaned pigs (P < 0.05).